The impact of ICT in schools :a landscape review - Rae Condie and Bob Munro (2007)
The impact of ICT in schools report was commissioned by Becta on behalf of the Department for Education and Skills (DfES) to analyse the impact of ICT on the schools sector across the United Kingdom. Over 350 published literature sources were consulted, ranging from policy documents, professional journals, research reports, reviews and digests to commercial publications. These have been listed in the bibliography although not all are referred to explicitly within the body of the report. This summary sets out the key messages from the literature, focusing firstly on the infrastructure to support the use of ICT, secondly on the impact on learning and teaching and, thirdly, on the extent to which ICT supports communication and links within and across schools and into the wider community. It concludes by drawing out several issues for further exploration and research.